Close enough? Professional closeness and safe caring - Andrew Kendrick; Mark Smith (Scottish Journal of Residential Child Care)
In countries around the world, residential child care has been rocked by scandals of abuse of children and young people by the people who were supposed to be caring for them. In the UK, in particular, the reaction to these revelations has been to implement a raft of measures that seek to ensure that nothing of the same nature or scale might happen again. However, there can be tensions between the implementation of such measures and the developmental and emotional needs of children and young people in residential care. In this paper, we outline recent policy and legislative developments and address some of the issues which we see as important in attempting to strike a balance between safe caring and quality caring, between professional closeness and abusive practice.